A Comparative Analysis on the Required Commercial Competences for Women Entrepreneurship Development in Selected Countries (European Journal of Marketing and Economics, 2025)
The scientific report is based on a desk research and an on-line survey done within an Erasmus + project, under Key Action 2 – Cooperation for innovation and the exchange of good practices, High Education Sector, named European Partnership for Social Inclusion and Creation of Skills for Women Entrepreneurship E-learning. The project is realized by three partner countries and it is focused on the social inclusion of women wishing to develop their own business in the area of trade and logistics through integration into entrepreneurship, acquiring practical skills and competences in order to generate financial, cultural and social value. A comparative analysis of the trade competences required for the development of women's entrepreneurship in the three partner countries is done. In the analysis, a study of the necessary literature in order to establish the theoretical and methodological framework of the study was initially carried out. Via a study of the existing competency models in the field of trade, the key necessary competencies for the realization of a trader have been identified. They serve to develop a questionnaire and they are the basis for the comparative analysis between the three partner countries.
Keywords: women's entrepreneurship, trade competences, comparative analysis.